Vitamin A and D levels in patients with filarial lymphedema and healthy volunteers in Puducherry, India - Venkatesan, Shakila; Sadhasivam, Anbusivam; Gnanasekaran, Vijayalakshmi; Periyathambi, Madhumidha; Moosan, Hisham; Kuttiatt, Vijesh Sreedhar (Frontiers in Nutrition, 2026)
Lymphatic filariasis (LF) is a parasitic disease caused by filarial nematode worms, transmitted by mosquitoes. Infection damages the lymphatic system which leads to limb lymphedema and hydrocele. LF continues to remain one of the major neglected tropical diseases. Patients with filarial lymphedema are prone to nutritional deficiencies due to poverty, poor nutrition, old age, and frequent adenolymphangitis. However, studies on micronutrient deficiencies in affected patients remain scarce. In this study, we aimed to assess the levels of vitamin A and D in patients visiting a specialized clinic for filarial lymphedema management. We recruited 40 patients and analyzed their vitamin A and D levels. In parallel, we also evaluated a set of 30 apparently healthy volunteers. Sociodemographic and clinical data were collected through a semi-structured interview using a proforma. Dietary data were recorded using a 24-h dietary recall method. Among 40 patients with filarial lymphedema, three had vitamin A deficiency, and so did six among the 30 healthy volunteers. Twenty patients and equal number of healthy volunteers were deficient in vitamin D. The study highlights vitamin D deficiency among patients with filarial lymphedema and healthy individuals. It is desirable to have nutritional counseling and multivitamin supplementation in the Morbidity Management and Disability Prevention (MMDP) component of the LF elimination program. Creating awareness about vitamin D deficiency among health care workers and public is also essential.